Lessons From the Pacific Islands – Adapting to Climate Change by Supporting Social and Ecological Resilience - Mcleod, Elizabeth; Bruton-Adams, Mae; Förster, Johannes; Franco, Chiara; Gaines, Graham; Gorong, Berna; James, Robyn; Posing-Kulwaum, Gabriel; Tara, Magdalene; Terk, Elizabeth (Frontiers in Marine Science, 2019)
By necessity Pacific Islands have become hubs of innovation, where climate strategies are piloted and refined to inform adaptation efforts globally. Pacific Island communities face increasingly severe climate impacts including sea-level rise, changing temperature and rainfall patterns, changes in food and water security, and social, cultural, and political impacts including loss of identity, climate-induced migration and threats to sovereignty. In response, communities in the region are leading climate adaptation strategies, often combining traditional practices and cutting-edge science, to build the resilience of their communities and ecosystems in the face of increasing climate risk. For example, communities are implementing resilient networks of marine protected areas using the best available science and strengthening tribal governance to manage these networks, experimenting with salt and drought tolerant crops, revegetating coastlines with native salt-tolerant plants, revitalizing traditional wells, and implementing climate-smart development plans. Often these efforts contribute to local development priorities and create co-benefits for multiple sustainable development goals (SDGs). These community efforts are being scaled up through provincial and national policies that reinforce the critical role that ecosystems play in climate adaptation and provide a model for the rest of the world. While adaptation efforts are critical to help communities cope with climate impacts, in some cases, they will be insufficient to address the magnitude of climate impacts and local development needs. Thus, there are inherent trade-offs and limitations to climate adaptation with migration being the last resort for some island communities.